2015
DOI: 10.1002/mnfr.201400840
|View full text |Cite
|
Sign up to set email alerts
|

Diet‐induced obesity causes metabolic impairment independent of alterations in gut barrier integrity

Abstract: None of our results provided any evidence that gut barrier function is a subject to dietary regulation and obesity per se seems not to cause gut barrier impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 42 publications
2
19
1
1
Order By: Relevance
“…In 2007, we found that changes in gut microbiota composition observed following HFD feeding were associated with increased plasma lipopolysaccharide (LPS) levels (the so‐called metabolic endotoxemia) , a phenomenon also extensively confirmed in other studies and in humans (Fig. ) , except in a recent study . The reason of this discrepancy is likely due to the difficulty to asses these critical parameters in complex matrix such as blood (e.g., false negative and LPS recoveries).…”
Section: Introductionmentioning
confidence: 69%
“…In 2007, we found that changes in gut microbiota composition observed following HFD feeding were associated with increased plasma lipopolysaccharide (LPS) levels (the so‐called metabolic endotoxemia) , a phenomenon also extensively confirmed in other studies and in humans (Fig. ) , except in a recent study . The reason of this discrepancy is likely due to the difficulty to asses these critical parameters in complex matrix such as blood (e.g., false negative and LPS recoveries).…”
Section: Introductionmentioning
confidence: 69%
“…Mono‐association of germfree mice with the gram negative Enterobacter cloacae , which was isolated from an obese human individual, induced obesity and elevated the systemic endotoxin concentration and inflammatory markers . However, diet‐induced obesity is not necessarily associated with impaired gut barrier integrity as recently demonstrated in three inbred mouse strains . C57BL/6J mice were fed the same lard‐based HFD used by Cani et al.…”
Section: Discussionmentioning
confidence: 96%
“…, but did not reveal any gut‐barrier dysfunction. Hence, it may be speculated that the observed differences between the two studies are due to differences in microbiota composition between the animal facilities of the two laboratories . Interestingly, in humans, obesity, and the obesity‐associated microbiota are not associated with an increased gut permeability suggesting a minor contribution of gut permeability to metabolic disease and endotoxemia.…”
Section: Discussionmentioning
confidence: 99%
“…Low-grade inflammation has frequently been discussed in obesity [56], [57], [58]. This observation together with the increased metabolites related to the arachidonic acid pathway in LHFD-fed GF mice led us to investigate plasma S-amyloid A levels.…”
Section: Discussionmentioning
confidence: 99%